Disease-specific U1 spliceosomal RNA mutations in mature B-cell neoplasms - Nadeu, Ferran; Shuai, Shimin; Clot, Guillem; Hilton, Laura K.; Diaz-Navarro, Ander; Martín, Silvia; Royo, Romina; Baumann, Tycho; Kulis, Marta; López-Oreja, Irene; Cossio, Manuel; Lu, Junyan; et al. (Leukemia, 2025)
Recurrent mutations in the third base of U1 spliceosomal RNA responsible for marked splicing and expression abnormalities have been described in chronic lymphocytic leukemia (CLL) and some solid tumors. However, the clinical significance of these mutations in large and independent CLL cohorts as well as their presence in other B-cell neoplasms is unknown. Here we characterized U1 mutations in 1670 CLL and 363 mature B-cell lymphomas. We confirmed that the g.3A>C U1 mutation is found in 3.5% of CLL, which conferred rapid disease progression independently of the main biological and clinical prognostic markers of the disease. Additionally, a recurrent g.9C>T mutation was found in 1.5% of CLL causing downstream splicing alterations and associated with adverse prognosis. We also identified a g.4C>T mutation in 10% of diffuse large B-cell lymphomas of the germinal center subtype and a g.7A>G mutation in 30% of EBV-negative Burkitt lymphomas, both of which altered the splicing pattern of multiple genes. This study reveals novel, recurrent, and tumor-specific U1 mutations in mature B-cell neoplasms with biological and prognostic implications, thus establishing U1 as a novel pan-B-cell malignancy driver gene.